2018
DOI: 10.1016/j.jenvman.2018.08.098
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characteristics of faecal sludge from VIP latrines and implications on pit emptying

Abstract: This work aims at characterizing the rheological properties of faecal sludge from Ventilated Improved Pit (VIP) latrines and their implication on pit emptying. Faecal sludge was sampled from 3 pit latrines located in the eThekwini Municipality (Durban, South Africa). Samples were taken at different positions within the pit. For each of the samples, measurements in the rheometer in triplicates were performed in order to determine their rheological properties, and their moisture and ash content were measured als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Indeed, the physical and chemical characteristics of the solid waste (mainly faecal matter and/or tissues) generated and stabilised through these decentralised wastewater treatment systems are different from those stabilised in commercial/pilot-scale wastewater treatment plants. Most of the research in this area has been conducted in response to initiatives such as Bill and Melinda Gates' 'Reinvent the Toilet Challenge' (RTTC) [2,3,56]. The innovative sanitary systems built under this initiative are required to operate in a waterless mode, whilst pursuing sustainable operation from the energy intensity point of view by recovering energy from solid waste [52].…”
Section: Review Of Micro-scale Human Faecal Sludge/faeces Treatment Studiesmentioning
confidence: 99%
“…Indeed, the physical and chemical characteristics of the solid waste (mainly faecal matter and/or tissues) generated and stabilised through these decentralised wastewater treatment systems are different from those stabilised in commercial/pilot-scale wastewater treatment plants. Most of the research in this area has been conducted in response to initiatives such as Bill and Melinda Gates' 'Reinvent the Toilet Challenge' (RTTC) [2,3,56]. The innovative sanitary systems built under this initiative are required to operate in a waterless mode, whilst pursuing sustainable operation from the energy intensity point of view by recovering energy from solid waste [52].…”
Section: Review Of Micro-scale Human Faecal Sludge/faeces Treatment Studiesmentioning
confidence: 99%
“…Pit emptying fees range from $35 - $95 per household in India and Kenya respectively, representing a substantive portion of an average monthly salary ranging from 12 to 125% ( Chowdhry and Kone, 2012 ; World Bank, 2019 ). Furthermore, due to the long storage periods, pit latrine sludge is stratified, with the fresher liquid layers towards the top and degraded consolidated sludge towards the bottom, reported to have densities of up to 1750 kg m −3 ( Radford and Sugden, 2014 ) where a considerable amount of added water is required to reduce sludge viscosity to facilitate a sufficient drop in pump head and power requirements ( Septien et al, 2018a ; Strande et al, 2014 ). This practice is, however, restricted by pit volume and water availability and incurs longer emptying times and greater transport costs which constitute 25% of faecal sludge management costs ( Steiner et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation of the rheological behaviour of faecal sludge is critical to inform on both the design and operation of dewatering or drying processes. Solids concentration is considered to be the defining factor which influences the rheology of faecal sludge (sewage sludge, pit latrine sludge, blackwater and faeces) by proportionally inducing shear stress to yield flow ( Cao et al, 2016 ; Septien et al, 2018a ; Thota Radhakrishnan et al, 2018a ; Thota Radhakrishnan et al, 2018b ; Woolley et al, 2014b ). However, faecal sludge rheological values differ according to type and literature on fresher unconsolidated faecal material is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ‘dry’ pits cannot be pumped using mechanical means. A rheological study of faecal sludge has shown that below 80% moisture content, pumping is not technically possible due to high frictional losses ( Septien et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%